2016
DOI: 10.1042/bst20150263
|View full text |Cite
|
Sign up to set email alerts
|

Cell surface recycling in yeast: mechanisms and machineries

Abstract: Sorting internalized proteins and lipids back to the cell surface controls the supply of molecules throughout the cell and regulates integral membrane protein activity at the surface. One central process in mammalian cells is the transit of cargo from endosomes back to the plasma membrane directly, along a route that bypasses retrograde movement to the Golgi. Despite recognition of this pathway for decades we are only beginning to understand the machinery controlling this overall process. Saccharomyces cerevis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 50 publications
0
23
0
Order By: Relevance
“…One well-studied protein that traffics in an Rcy1-dependent route through early endosomes is the SNARE protein Snc1. Unlike the major endocytic recycling pathways in mammalian cells, return of endocytosed Snc1 to the cell surface is thought to occur mainly via transport from early endosomes back to the TGN/Golgi along a retrieval pathway before transit to the cell surface ( Tanaka et al, 2011 ; Sebastian et al, 2012 ; Feyder et al, 2015 ; MacDonald and Piper, 2016 ). This model is rooted in observations showing that a portion of GFP-Snc1 colocalizes with Sec7 (an Arf exchange factor that marks the TGN), and that Snc1 quickly accumulates intracellularly when proteins required for transport through the Golgi are acutely inactivated ( Lewis et al, 2000 ; Chen et al, 2005 ; Robinson et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One well-studied protein that traffics in an Rcy1-dependent route through early endosomes is the SNARE protein Snc1. Unlike the major endocytic recycling pathways in mammalian cells, return of endocytosed Snc1 to the cell surface is thought to occur mainly via transport from early endosomes back to the TGN/Golgi along a retrieval pathway before transit to the cell surface ( Tanaka et al, 2011 ; Sebastian et al, 2012 ; Feyder et al, 2015 ; MacDonald and Piper, 2016 ). This model is rooted in observations showing that a portion of GFP-Snc1 colocalizes with Sec7 (an Arf exchange factor that marks the TGN), and that Snc1 quickly accumulates intracellularly when proteins required for transport through the Golgi are acutely inactivated ( Lewis et al, 2000 ; Chen et al, 2005 ; Robinson et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…This model is rooted in observations showing that a portion of GFP-Snc1 colocalizes with Sec7 (an Arf exchange factor that marks the TGN), and that Snc1 quickly accumulates intracellularly when proteins required for transport through the Golgi are acutely inactivated ( Lewis et al, 2000 ; Chen et al, 2005 ; Robinson et al, 2006 ). Indeed, yeast are not currently known to have a direct surface recycling pathway from early endosomes to the cell surface that bypasses a retrieval step to the TGN ( MacDonald and Piper, 2016 ). Here we find that yeast do have such a recycling pathway from early endosomes to the plasma membrane (EE>PM).…”
Section: Introductionmentioning
confidence: 99%
“…Early endosomes are crucial branch points from which cargo may be trafficked in a retrograde fashion to the Golgi apparatus through the action of the Retromer and GARP complexes, sorted into intralumenal vesicles by ESCRT, or recycled directly to the plasma membrane. Direct recycling is known to occur in yeast, though the precise mechanisms are not completely understood (65). We hypothesized that perturbations in ESCRT and other pro-degradation factors shift the dynamic equilibrium of the endosomal population of ROMK toward increased recycling.…”
Section: Identification Of a Romk Variant Suitable Formentioning
confidence: 99%
“…Endocytosis involves the internalisation of surface proteins from the plasma membrane (PM) in vesicles that are transported to endosomal compartments. Endocytic trafficking from the PM provides a layer of control, where cargoes can either be temporarily removed from the surface and recycled back or permanently removed via their ubiquitin-mediated degradation in the lysosome (MacDonald and Piper, 2016). Endocytic events can be relatively specific, for example the internalisation of a single receptor, or much more general, where a large and varied cohort of proteins are endocytosed.…”
Section: Introductionmentioning
confidence: 99%
“…Proteins that are not destined for degradation can recycle back to the surface, including routes that return material to the surface via the trans-Golgi network (TGN) through dedicated machineries that interact with cargoes for recycling (McNally and Cullen, 2018). Recycling can also occur directly from early endosomes or indirectly, first traversing defined recycling endosomes (MacDonald and Piper, 2016). Endosomal organisation and recycling mechanisms in yeast are less clear (Ma and Burd, 2019), however, it was recently shown that although retrograde recycling of the yeast exocytic v-SNARE protein Snc1 is perturbed by deubiquitination (Xu et al, 2017), some cargo recycling is triggered by deubiquitination .…”
Section: Introductionmentioning
confidence: 99%